Grants Versus Tax Sharing: the Extent of Central Government Control - Graeme Roy (European Regional Science Association (ERSA), 2006)
By spending more than they are able to raise, sub-central governments typically depend heavily upon central transfers to meet their expenditure responsibilities. While grants remain the most popular method of transfer, the possible use of tax sharing arrangements as an alternative method of finance has received increased attention in recent years. In nearly all tax sharing systems that we are aware of, central governments play a dominant role in determining the amount of revenue each sub-central unit receives from the shared source. It has therefore, become common in the academic literature to interpret grants and tax sharing as equivalent tools of central fiscal control over sub-central tiers. However, we caution against this. In our paper, we demonstrate that only in a particular special case is it correct to conclude that the level of central control of sub-central finances is the same under a system of grants as it is under tax sharing.
Keywords: 330